Comparison of Red Betel Leaf Decoction and Aloe Vera Decoction on Decreased Sugar Levels in Patients with Diabetes Mellitus at Setia Janji Health Center - Herviza Wulandary Pane; Bima Suryantara; Juda Julia Kristiarini (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Diabetes Mellitus is the third most common cause of death after cancer and cardiovascular disease in people aged 30-70 years (WHO 2016). The aim of the study was to compare the effect of red betel leaf decoction and aloe vera decoction on reducing blood sugar levels in people with diabetes mellitus at the Setia Janji Health Center. This research is a quantitative research. In this study the researchers used the Pre-Experiment research design with a One-Group Pretest-Posttest Design with a control approach. The research was carried out in February 2023 until it was completed at the Setia Janji Health Center. With a Sample of 40 People. Bivariate analysis using Bivariate Analysis was used to see how far the influence of each independent variable on the dependent variable used the Shapiro-Wilk data normality test and the Paired T-test paired samples.The study obtained that the average difference in blood sugar levels of DM patients before and after being given red betel leaf decoction was 82.90 mg/dL with a standard deviation of 28.069 mg/dL. The average difference in blood sugar levels of DM patients before and after being given red betel leaf decoction was 45.30 mg/dL with a standard deviation of 22.614 mg/dL. The results of the Mann Whitney statistical test obtained p = 0.000, where the p value ≤ 0.05, statistically it means that there is a difference in the average decrease in blood sugar levels given red betel leaf decoction (Piper crocatum) and aloe vera decoction. in people with diabetes mellitus at the Setia Janji Health Center. There is support from midwives in providing counseling about the benefits of decoction of red betel leaves and aloe vera as an alternative to herbal medicine in helping lower blood sugar levels in people with diabetes mellitus. Keywords : Aloe Vera, Decrease in KGD, DM, Red Betel Leaf